1995
DOI: 10.1021/cm00056a015
|View full text |Cite
|
Sign up to set email alerts
|

Novel Blue Electroluminescent Polymers with Well-Defined Conjugation Length

Abstract: Light emission from pale blue to greenish blue is successfully obtained from the diodes made of the trimethylsilyl-, monoalkoxy-, and dialkoxy-substituted polymers with welldefined conjugation length containing phenylenevinylene units. The conjugation length is adjusted by incorporating the nonconjugated spacer group in the backbone. The polymers are organic soluble and allow the fabrication of the light-emitting diode by spinning without further thermal processes. The fabricated devices show typical diode cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 0 publications
2
64
0
Order By: Relevance
“…Both copolymers display absorption spectra very similar to those of their respective model compounds as a result of the similarity in chromophores. The absorption peaks of copolymers 1 and 6 are qualitatively similar; the former has a maximum absorption at a longer wavelength because of the longer conjugation length of its chromophore, 390 nm (1) versus 370 nm (6).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Both copolymers display absorption spectra very similar to those of their respective model compounds as a result of the similarity in chromophores. The absorption peaks of copolymers 1 and 6 are qualitatively similar; the former has a maximum absorption at a longer wavelength because of the longer conjugation length of its chromophore, 390 nm (1) versus 370 nm (6).…”
Section: Resultsmentioning
confidence: 92%
“…There have been reports on a series of conjugated± nonconjugated copolymers (CNCPs) containing uniformly alternating conjugated rigid and nonconjugated flexible blocks which exhibit blue electroluminescence with a spectral maximum at 465 nm [3,4,5]. Zyung et al [6] and Hosokawa et al [7] reported other series of CNCPs also emitting blue light. Zhang et al [8] have shown that PPV obtained by partial conversion of the precursor polymer (a system that may also be regarded as a CNCP with a broad distribution of conjugation lengths), emitted light whose wavelength maximum was slightly blue-shifted from that of the nominally fully conjugated PPV.…”
mentioning
confidence: 99%
“…The feasibility and processibility of large-scale application using organic polymers spurred research into the use of p-conjugated polymers in blue light emission. [4][5][6][7][8][9][10] Blue EL from poly(p-phenylene) [5] and poly(alkyfluorene) [4,6] was observed, but they showed rather poor processibility and mechanical properties for the device. Therefore, many other materials have been utilized for blue EL generation.…”
Section: Introductionmentioning
confidence: 99%
“…Nonconjugated side chain polymers, conjugatednonconjugated multiblock copolymers, and also sterically hindered conjugated polymers have been developed for blue light emission. [8][9][10] In this paper, we report the synthesis and the characterization of the light-emitting properties of new blue-light emitting polymers (POFB-MEH-PPV, POFB-PF, and POFB-PK) with electron accepting octafluorobiphenyl moieties introduced into the polymer backbone. To improve the EL efficiency and obtain blue light emission from the conjugated polymer, balanced injection of holes and electrons from each of the electrodes, and confined conjugation lengths are needed, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis from the solution routes has been on retaining a stable amorphous structure and solubility of the polymer for processing. [1][2][3] From the CVD route, a-chlorinated or a-brominated poly(p-xylylene) was first deposited and then subsequent dehydrohalogenation converted the polymer to PPV with much crystallinity. [4] The CVD route and the properties of the PPV films have been well characterized.…”
Section: Introductionmentioning
confidence: 99%